2011
DOI: 10.3390/s110505360
|View full text |Cite
|
Sign up to set email alerts
|

Microfabrication and Applications of Opto-Microfluidic Sensors

Abstract: A review of research activities on opto-microfluidic sensors carried out by the research groups in Canada is presented. After a brief introduction of this exciting research field, detailed discussion is focused on different techniques for the fabrication of opto-microfluidic sensors, and various applications of these devices for bioanalysis, chemical detection, and optical measurement. Our current research on femtosecond laser microfabrication of optofluidic devices is introduced and some experimental results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 107 publications
0
13
0
1
Order By: Relevance
“…Surface Plasmon excitation methods: a) Otto configuration and b) Kretschmann configuration of prism coupled propagating surface plasmon polariton (SPP); c) grating coupled SPP; d) near‐field coupled localized surface plasmon resonance (LSPR). Reproduced with permission: (a,b) Copyright 2006, Cambridge University Press; (c) under Creative Commons 3.0 license Copyright 2011, MDPI, and (d) Copyright 2006, The American Physical Society.…”
Section: Surface Plasmons and Plasmonic Lithographymentioning
confidence: 99%
“…Surface Plasmon excitation methods: a) Otto configuration and b) Kretschmann configuration of prism coupled propagating surface plasmon polariton (SPP); c) grating coupled SPP; d) near‐field coupled localized surface plasmon resonance (LSPR). Reproduced with permission: (a,b) Copyright 2006, Cambridge University Press; (c) under Creative Commons 3.0 license Copyright 2011, MDPI, and (d) Copyright 2006, The American Physical Society.…”
Section: Surface Plasmons and Plasmonic Lithographymentioning
confidence: 99%
“…For that, this configuration is the most common approach. These two configurations are illustrated in Figure. 3 10 :…”
Section: Excitation Of Surface Plasmonmentioning
confidence: 99%
“…Wavelength tuning in the visible spectral range, commonly known as color filtering, is particularly important for applications, such as a color filter consisting of an array of annular apertures in a gold film for transmission measurement [12], a multilayered structure incorporating a subwavelength metal-dielectric grating for better reflection resonance and color effects [13], excitation of surface plasmonic effects in nanostructured materials [14][15][16], and plasmonic color filters adopting freestanding resonant membrane waveguides [17]. Most of these reported components are either relatively large in volume for use in free-space optics, costly in the fabrication techniques, or are mostly incompatible with integrated systems, especially for the case of biomedical applications, for example, a lab-on-a-chip platform, where footprint and the compatibility with the fluidic environment are crucial [18]. Yu et al showed an optical diffraction grating using multiphase droplets on a microfluidic chip, which produces different colors as a color filter [19].…”
Section: Introductionmentioning
confidence: 99%